Indications for Dental Specialists for Treating Obstructive Sleep Apnea with Mandibular Advancement Devices: A Narrative Review - Antonino Lo Giudice; Salvatore La Rosa; Vincenzo Ronsivalle; Gaetano Isola; Marco Cicciù; Giulio Alessandri-Bonetti; Rosalia Leonardi (International Journal of Dentistry)
Obstructive sleep apnea (OSA) syndrome is characterized by repeated airway collapse during sleep. It determines cardiovascular, pulmonary, and neurocognitive consequences and is associated with several daytime and nighttime symptoms that influence the patient’s quality of life. The contribution of the dental specialist in the clinical management of OSA patients entails participating in the screening process as diagnostic sentinels and providing adequate treatment using mandibular advancement devices (MADs). Since the treatment of OSA requires a multidisciplinary approach, including different medical specialists, dentists should have a comprehensive understanding of medical and dental factors that influence the strategy and effectiveness of OSA treatment with MAD. Such expertise is crucial in determining the appropriate treatment indications and helps clinicians establish a consolidated position within the multidisciplinary OSA team. In this regard, this review summarizes the evidence of the clinical indications for MAD treatment and provides the dental specialist with helpful information about medical, functional, and other relevant factors that should be considered during diagnosis, treatment plan, and follow-up stages. Information retrieved was organized and discussed, generating specific domains/queries oriented to the clinical management of OSA patients from the clinical perspective of dental specialists.